2023
DOI: 10.3390/ijms24043257
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Alleviates Doxorubicin-Induced Myocardial Injury and Fibrosis by Eliminating Oxidative Stress and Mitochondrial Damage via Promoting Nrf-2 Pathway Activation

Abstract: Doxorubicin (DOX)-related cardiotoxicity has been recognized as a serious complication of cancer chemotherapy. Effective targeted strategies for myocardial protection in addition to DOX treatment are urgently needed. The purpose of this paper was to determine the therapeutic effect of berberine (Ber) on DOX-triggered cardiomyopathy and explore the underlying mechanism. Our data showed that Ber markedly prevented cardiac diastolic dysfunction and fibrosis, reduced cardiac malondialdehyde (MDA) level and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…In mouse embryonic fibroblast cells (NIH‐3 T3) pretreated with LPS (1 μg/mL) for 1 h, treatment with berberine‐modified ZnO nano‐colloids hydrogel ZnO‐Ber (1 mg/mL) for 4 h significantly up‐regulated antioxidant stress factors (Nrf2, HO‐1, NQO1), reduced MDA, and increased SOD (Yin et al, 2022). Pretreatment with berberine (1 μM) for 24 h inhibited ROS and MDA production and increased SOD activity and the mitochondrial membrane potential in doxorubicin‐challenged cardiac fibroblasts by activating the nuclear erythroid factor 2‐related factor 2 (Nrf2)‐mediated pathway (Wang et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In mouse embryonic fibroblast cells (NIH‐3 T3) pretreated with LPS (1 μg/mL) for 1 h, treatment with berberine‐modified ZnO nano‐colloids hydrogel ZnO‐Ber (1 mg/mL) for 4 h significantly up‐regulated antioxidant stress factors (Nrf2, HO‐1, NQO1), reduced MDA, and increased SOD (Yin et al, 2022). Pretreatment with berberine (1 μM) for 24 h inhibited ROS and MDA production and increased SOD activity and the mitochondrial membrane potential in doxorubicin‐challenged cardiac fibroblasts by activating the nuclear erythroid factor 2‐related factor 2 (Nrf2)‐mediated pathway (Wang et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with berberine (1 μM) for 24 h inhibited ROS and MDA production and increased SOD activity and the mitochondrial membrane potential in doxorubicin-challenged cardiac fibroblasts by activating the nuclear erythroid factor 2-related factor 2 (Nrf2)-mediated pathway (Wang et al, 2023).…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many natural product components extracted from medicinal plants have been proven to inhibit CAF activation. Berberine (Ber), an isoquinoline quaternary alkaloid derived from rhizoma coptidis, could exert anti-inflammation, anti-oxidative, and anti-cancer activities. , Recent research showed that Ber could inhibit α-SMA expression of quiescent fibroblasts and CAF-mediated ECM deposition. , Moreover, Ber also was proven to down-regulate the expression level of ZEB1 and Snail as well as block TGF-β/Smad2/3-mediated tumor metastasis. , Hence, Ber might be a potential component to modulate TME by inhibiting CAF-induced tumor development. Furthermore, the hormone receptor modulators (tamoxifen, letrozole, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recent research showed that Ber could inhibit α-SMA expression of quiescent fibroblasts and CAF-mediated ECM deposition. 11,12 Moreover, Ber also was proven to down-regulate the expression level of ZEB1 and Snail as well as block TGF-β/Smad2/3-mediated tumor metastasis. 13,14 Hence, Ber might be a potential component to modulate TME by inhibiting CAF-induced tumor development.…”
Section: Introductionmentioning
confidence: 99%